A woman with a normal uterus and duplicated cervices: A case report and review of a Müllerian anomaly - Kinjal Mukesh Mehta; Ellen Elizabeth Wilson (Elsevier, 2023)
Müllerian duct anomalies (MDAs) are common and can lead to problems with menstrual flow, pregnancy, and fertility. This is a case report of a 21-year-old woman with an incidentally found bicollis uterus with vaginal septum, which challenges the previously held principles of embryology and further supports the current theories that explain these transitional forms of female reproductive anomalies. Due to the irregularity found during the physical examination, detailed imaging with magnetic resonance helped to delineate the anatomy of the reproductive system and genitourinary (GU) tract, uncovering and confirming the anatomical abnormality. Due to the concern for future implications, especially during pregnancy, surgical excision of the vaginal septum was performed. This unique anomaly bolsters a discussion on the outcomes and implications of these unknown rare anomalies in various settings.